Persistence in University Continuing Education Online Classes - Frydenberg, Jia (International Review of Research in Open and Distributed Learning, 2007)
This study presents persistence and attrition data from two years of data collection. Over the eight quarters studied, the persistence rate in online courses was 79 percent. The persistence rate for similar onground courses was 84 percent. The drops for both course modalities were disaggregated by the time of the request for withdrawal: before course start, during the initial week, and during instruction. There was a significant difference between online and onground requests for withdrawals during the initial week. There was no significant difference between online and onground drop rates after the start of instruction, leading to the conclusion that differences in instruction online and onground was unlikely to be a major influencing factor in the student’s decision to drop.